The Effect of Melt Infiltration on Metagranitic Rocks: the Snieznik Dome, Bohemian Massif. (6th February 2019) - Štípská, P; Hasalová, P; Powell, R; Závada, P; Schulmann, K; Racek, M; Aguilar, C; Chopin, F
Abstract: Highly deformed banded phengite–biotite metagranite from the Snieznik dome in the Bohemian Massif has been modified locally to have stromatic, schlieren or nebulitic textures typical of migmatites. This occurred mostly along subvertical deformation zones at eclogite-facies conditions, at a scale of several centimetres to several metres, mostly parallel to the foliation. The transition from banded to migmatite types of orthogneiss is marked by an increase in the amount of phases interstitial along grain boundaries in the dynamically recrystallized monomineralic feldspar and quartz aggregates, and by increasing consumption of recrystallized K-feldspar grains by fine-grained plagioclase and quartz, as well as myrmekite (intergrowth of Pl−Qz). The new minerals are in textural equilibrium with phengite. The myrmekite, quartz and feldspars can be coarse-grained (grain size ≤0·5 cm). These features are considered to be the result of grain-scale melt infiltration that caused dissolution–reprecipitation along grain boundaries in the presence of phengite. The infiltration was pervasive at the grain scale, but localized at hand-specimen to outcrop scales. All the rock types have the same mineral assemblage of Grt−Ph−Bt−Ttn−Kfs−Pl−Qz±Rt±Ilm; they have similar garnet, phengite and biotite compositions, and based on mineral equilibria modelling we infer equilibration at a pressure of 1·5–1·7 GPa and a temperature of 690–740°C. Because the rocks are inferred to be H2 O-undersaturated and above the temperature conditions of the wet solidus, infiltration must have involved a hydrous melt, as opposed to an H2 O fluid. Stability of melt-bearing mineral assemblages and mineral compositions are almost independent of the melt proportion in the system, thus explaining the identical assemblage and mineral compositions observed in all the migmatite types. This precludes the estimation of the amount of melt infiltrated. Migmatite textures, however, suggest that variable degrees of melt–rock interaction occurred, being low in the banded migmatite types and higher in the nebulitic and schlieren types. Retrograde equilibration was largely restricted to retrograde zoning in phengite, garnet and plagioclase, and crystallization of biotite around phengite and garnet, presumably in a continuous reaction consuming melt. This may have occurred down to ∼0·7–1·0 GPa. According to Sr–Nd isotope data, the infiltrating melt is probably derived from similar rocks, structurally beneath the observed ones. The infiltration may have facilitated exhumation of a 2 km wide structural domain from ∼1·7 to ∼0·7 GPa, within which are the subvertical deformation zones along which the infiltration occurred.